THE RELATIONSHIP BETWEEN UNDERSTANDING BASIC CONCEPTS, CREATIVITY PROBLEM SOLVING, AND UTILIZATION OF LEARNING RESOURCES WITH STUDENTS MATHEMATICS LEARNING OUTCOMES - Rahma Damayanti; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
This research aims to know if there is a positive and significant of Relationship between Understanding Basic Concepts, Creativity Problem Solving, and Utilization of Learning Resources with Students Mathematics Learning Outcomes in Class VII in State Junior High School (SMP Negeri) 1 Bambanglipuro Bantul Regency of Even Semester Academic Year of 2016/2017. The sample class in SMP Negeri 1 Bambanglipuro Bantul in 2016/2017 consists of 7 classes. A sample class is a class VII D using random sampling. Data collection instruments using an Understanding Basic Concepts test, Creativity Problem-Solving test, questionnaires Utilization of Learning Resources, and mathematics achievement test. Test research instruments used validity, different test power, and Reliability test. Analysis prerequisite test, including normality test, linearity test, and independent test. Data analysis for hypothesis testing using correlation analysis and multiple regression analysis. The results showed a positive and significant relationship between Understanding Basic Concepts, Creativity Problem Solving, and Learning Resources with Mathematics Learning Outcomes. The significant level of 5%, v1=3, v2=23, Fcount=4.3028 and Ftable=3,0279,Fcount> Ftable with multiple correlation coefficient of R2 = 0,3595, and multiple regression equation there variable is = -81,06 + 0,3948X1 + 1,3489X2 + 1,0474X3. Donations are relatively X1=26,8851%,Â  X2=37,6980%,Â  X3=35,4168%, with multiple determination coefficient of 0,750 and the effective contribution X1=9,6647%, X2=13,5518%, X3=12,7317%.